Time-varying stability and vibration properties of a pyrotechnic ejection plate in narrow space. (15th February 2023) - Liu, Dong; Yao, Guo
Highlights: Considered the particular circumstance of the pyrotechnic plate in axial airflow. Established the nonlinear dynamic model of the plate with variable velocity. A period of instability of the plate was observed during pyrotechnic ejection. The amplitude of the plate at the unstable period is significantly enlarged. Abstract: This work simulates the pyrotechnic launch process which is commonly seen in aerospace engineering, and the dynamic responses of the projectile during pyrotechnic ejection are analyzed by studying the aeroelastic stability and nonlinear vibration of a rectangular plate subjected to time-varying axial blast load in a narrow space. During the launch, the plate is accelerated under the explosion effect, which makes the plate and airflow in narrow space a complicated time-varying fluid structure interaction system. The change of the plate velocity is derived from the momentum theorem. Considering the Von Karman nonlinear thin plate theory and the linear potential flow theory, the governing equation of the pyrotechnic ejection plate in narrow space is established. In the process of solving the equation, the Hamilton's principle and the assumed mode method are employed. By applying the generalized eigenvalue method to linear time-varying system, the variations of the natural frequencies of the plate during pyrotechnic ejection are studied, from which the stability mechanism of the system is obtained. For nonlinear vibration of the system, the displacement time responses of the plate during pyrotechnic ejection are discussed by employing the Runge-Kutta method. From the results, the plate loses stability rapidly when the explosion occurs, and then with the increase of the velocity of the plate, the plate exhibits the flutter instability. In the process of pyrotechnic ejection, the amplitude jumping phenomenon of the plate is observed. Besides, the explosion strengthen, explosion position, slit height and aspect ratio of the plate have significant effects on the stability and displacement jumping amplitude of the pyrotechnic ejection plate.